La ascension del lucero de la tarde - Mull, Brandon, 1974-; Belaustegui, Ines (Barcelona : Roca Editorial, 2010)
When Kendra and Seth return to Fablehaven, they discover that Grandpa Sorenson has asked three specialists to protect the property from the Society of the Evening Star, a group determined to steal an artifact of great power from the preserve.
Sequel to: Fablehaven.
Keywords: Magic -- Juvenile fiction; Grandparents -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Spanish language materials